2017
DOI: 10.3390/app7070692
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation with Glomus mosseae Improves the Growth and Salvianolic Acid B Accumulation of Continuously Cropped Salvia miltiorrhiza

Abstract: Salvia miltiorrhiza (S. miltiorrhiza) Bunge is one of the most economically important medicinal crops in China. In traditional Chinese medicine, its root is used as an important ingredient in formulas for treatment of atherosclerosis-related disorders. The continuous cropping of S. miltiorrhiza increases the proportion of dried seedlings and decreases the biomass of the shoots and roots and the contents of active components. In this study, three field experiments were conducted to investigate the effects of Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…Arbuscular mycorrhizal fungi (AMF), which obtain nutrients through infecting host plant root systems and are the most widely distributed symbiont, can infect the root systems of over 80% of vascular plants ( Li, 1998 ). The hypha of AMF can serve as an important channel for soil nutrients entering plants, hence it can also promote the absorption of nutrients by host plants ( Karagiannidis et al, 2002 ), promote plant growth, yield, and quality ( Bowles et al, 2016 ; Rozpądek et al, 2016 ), improve plant photosynthetic capacity and PSII function ( Chen et al, 2017a ; Mathur et al, 2018 ), as well as accelerate plant growth and enhance plant stress resistance through impacting root exudation ( Chen et al, 2017b ). Some studies also found that AMF could improve plant tolerance to heavy metal pollution ( Del et al, 1999a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Arbuscular mycorrhizal fungi (AMF), which obtain nutrients through infecting host plant root systems and are the most widely distributed symbiont, can infect the root systems of over 80% of vascular plants ( Li, 1998 ). The hypha of AMF can serve as an important channel for soil nutrients entering plants, hence it can also promote the absorption of nutrients by host plants ( Karagiannidis et al, 2002 ), promote plant growth, yield, and quality ( Bowles et al, 2016 ; Rozpądek et al, 2016 ), improve plant photosynthetic capacity and PSII function ( Chen et al, 2017a ; Mathur et al, 2018 ), as well as accelerate plant growth and enhance plant stress resistance through impacting root exudation ( Chen et al, 2017b ). Some studies also found that AMF could improve plant tolerance to heavy metal pollution ( Del et al, 1999a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…1e), and tanshinone IIA (Fig. 1f) in the roots were determined using the methods described by Chen et al (2017b). Roots harvested from experimental plants were dried at 40°C for 48 h. The dried roots were ground in a standard grinder and then passed through a 40-mesh sieve.…”
Section: Quanti Cation Of Bioactive Compounds In Rootsmentioning
confidence: 99%
“…AMF can also increase the contents of bioactive compounds such as terpenoids, alkaloids, and phenolics in many economically and industrially signi cant crops and herbs [13][14][15] . Our previous study also showed that inoculation with Glomus mosseae improves growth and salvianolic acid B accumulation in continuously cropped S. miltiorrhiza 14 . However, mycorrhizal e ciency varies with soil fertilizers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMF can also increase the contents of bioactive compounds such as terpenoids, alkaloids, and phenolics in many economically and industrially significant crops and herbs 13 15 . Our previous study also showed that inoculation with Glomus mosseae improves growth and salvianolic acid B accumulation in continuously cropped S. miltiorrhiza 15 . However, mycorrhizal efficiency varies with soil fertilizers.…”
Section: Introductionmentioning
confidence: 99%